Political Communication Patterns of Young Adults in Germany - Datts, Mario; Wiederholz, Jan-Erik; Schultze, Martin; Vowe, Gerhard (Frontiers in Communication, 2021)
While the political communication and participation activities of young adults are changing, this is often not adequately captured by research due to a too narrow conceptualization of the phenomenon. Our approach conceptualizes political communication as activities comprising the reception of political content, interpersonal communication regarding political issues and political participation. We incorporated both analog and digital media, as well as different forms of political participation, to reflect the complex reality of political communication activities of young adults in the digital age. On the basis of a sample from 2013, we investigated the patterns of political communication of young adults (ages 18–33 years). This age group represents the first generation to have grown up under the ubiquitous influence of the internet and other modern information technologies. In addition, we examined factors influencing the formation of different political communication patterns of this generation. Results of cluster analyses demonstrated that young adults should not be seen as a homogeneous group. Rather, we found six communication types. Interestingly, no online-only type of political communication was revealed, By applying multinomial logistic regression analysis, we were able to demonstrate that socio-demographic variables, individual resources and cognitive involvement in politics influence the likelihood of belonging to more active political communication types. The present study investigated various information and communication opportunities of young adults, and is rare in terms of the richness of data provided. Our conceptual innovative approach enables a better understanding of young adults’ complex political communication patterns. Moreover, our approach encourages follow-up research, as our results provide a valuable starting point for intergenerational comparisons regarding changes in political engagement among young adults in Germany, as well as for cross-country analysis regarding different generations of young adults.